Forensic Efficiency Estimation of a Homemade Six-Color Fluorescence Multiplex Panel and In-Depth Anatomy of the Population Genetic Architecture in Two Tibetan Groups - Liu, Yanfang; Cui, Wei; Jin, Xiaoye; Wang, Kang; Mei, Shuyan; Zheng, Xingkai; Zhu, Bofeng (Frontiers in Genetics, 2022)
The genetic information of Chinese Tibetan group has experienced significant natural selection, and has been a long-standing research hotspot among population geneticists and archaeologists. Herein, 309 unrelated individuals from two Tibetan groups living in China’s Qinghai Province (CTQ) and Tibet Autonomous Region (CTT) were successfully genotyped using a new homemade six-color fluorescence multiplex panel, which contained 59 autosomal deletion/insertion polymorphisms (au-DIPs), 2 mini STRs, 2 Y-DIPs, and one Amelogenin gene. The cumulative match probability and cumulative exclusion probability of this new panel in these two groups were 1.9253E-27 and 0.999997, as well as 1.5061E-26 and 0.99999895, respectively. Subsequently, a comprehensive population genetic analysis of Tibetans was carried out based on the 59 au-DIPs in this new panel. The multitudinous statistical analysis results supported that Tibetan groups have close genetic relatedness with East Asia populations. Gene flow between the Tibetan groups and the Finnish population was identified under the 8 inferred migration events of the Maximum likelihood tree reconstructed through 91 au-DIPs. These discoveries shed light on that this homemade system can be an excellent tool for forensic individual identification and paternity testing in Chinese Tibetan groups, and give us an important insight for further perfecting the genetic landscape of Chinese Tibetans.